A Systematic Review and Meta-Analysis of Ocular and Periocular Basal Cell Carcinoma with First-Time Description of Dermoscopic and Reflectance Confocal Microscopy Features of Caruncle Basal Cell Carcinoma - Martina Caviglia; Shaniko Kaleci; Pasquale Frascione; Miram Teoli; Maria Concetta Fargnoli; Giovanni Pellacani; Victor Desmond Mandel (Diagnostics)
Background: Basal cell carcinoma (BCC) of the ocular and periocular region is characterized by a painless progressive extension. An early diagnosis can limit the extent of facial tissue involvement and subsequent resection resulting in better cosmetic and functional results. Objectives: The aim is to provide the largest and most up-to-date overview of ocular and periocular BCCs. We also reported the first case of caruncle BCC investigated by dermoscopy and reflectance confocal microscopy (RCM). Methods: A systematic review and meta-analysis (Prospero ID CRD583032) were carried out by searching PUBMED–MEDLINE, including all articles with a full-text English version and with BCCs in eyelids, medial and lateral canthus, caruncle, conjunctiva, and orbit. The following data were collected: authors, year, title and type of publication, medical specialization, number, sex, age and comorbidities of the patients, anatomic localization of the disease, clinical and dermoscopic aspect, histological examination, and treatment. Results: We identified 731 articles through a database search, of which 236 articles matched our inclusion criteria. A total of 71.730 patients with ocular and periocular BCCs were included in the present study, and all data collected were reported in a dataset. Most of the articles included were described by ophthalmologists (67.5%), dermatologists (11.2%), or plastic surgeons (5.6%). The proportional meta-analysis revealed varying significance and heterogeneity for each type of study included. Conclusions: BCC more frequently affects the lower eyelid. The most common BCC subtype of ocular and periocular area is the nodular form. Limited data are available concerning the application of dermoscopy and RCM in this area. RCM may be particularly useful for early diagnosis, mapping, and treatment monitoring of ocular and periocular BCCs. Surgery still remains the first-choice treatment.